Child-centered play therapy as an intervention for externalizing problem behaviors: An analysis of outcomes and therapeutic skills - Bengwasan, Peejay D. (Animo Repository, 2020)
The present study examined the effectiveness of Child Centered Play Therapy (CCPT) for school aged children who present with externalizing problem behaviors. 23 participants were given 8 weekly individual sessions. For each participant, a parent accomplished the Child Behavior Checklist (CBCL) and a teacher accomplished the Teacher Rating Form (TRF) at 3 timepoints: Pre-Therapy, Post-Therapy and 1 month Follow Up. Separate repeated measures ANOVAs performed on these outcomes revealed significant differences of Externalizing Problems across timepoints for the CBCL and TRF Externalizing Problems scale and its two subscales (Rule-Breaking and Aggressive Behaviors). A large effect size was obtained from such analyses, which indicate much improvement in behaviors in school and at home. The study likewise examined underlying processes of CCPT, particularly the use of therapeutic skills. Across 8 sessions, separate Friedman tests with Wilcoxon signed rank test as post hoc analysis revealed that there were significant differences in the usage of tracking, reflecting feelings, reflecting content and limit setting. This indicates a dynamic nature of using such skills in maintaining the therapeutic relationship in short term CCPT. Keywords: Child-Centered Play Therapy, externalizing problem behaviors, outcomes, therapeutic skills